2009
DOI: 10.1103/physreva.79.054101
|View full text |Cite
|
Sign up to set email alerts
|

Two destructive effects of decoherence on Bell inequality violation

Abstract: We consider a system of two spin-1 2 particles, initially in an entangled Bell state. If one of the particles is interacting with an environment (e.g., a collection of N independent spins), the two-particle system undergoes decoherence. Using a simple model of decoherence, we show that this process has two consequences. First, the maximal amount by which the CHSH inequality is violated decays to zero. Second, the set of directions of measurement for which the inequality is violated is reduced in the course of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The research of quantum correlation dynamics in noise environments is a basic and significant problem in the quantum decoherence theory. In the last twenty years the decoherence dynamics of quantum correlations including quantum entanglement [1][2][3][4][5][6][7], Bell nonlocality measured by the violation of the famous Clauser-Horne-Shimony-Holt (CHSH) inequality [8] and its relation to quantum entanglement [9][10][11][12][13][14][15][16], quantum discord [17,18] for the bipartite systems have been studied intensely, which is also generalized to the multipartite system for quantum entanglement [19][20][21][22][23][24][25][26] and the Bell nonlocality [27][28][29][30][31][32][33][34]. It has been shown that the Bell nonlocality may be stricter than quantum entanglement in the bipartite system [9][10][11][12][13][14][15][16] and tripartite system [32].…”
Section: Introductionmentioning
confidence: 99%
“…The research of quantum correlation dynamics in noise environments is a basic and significant problem in the quantum decoherence theory. In the last twenty years the decoherence dynamics of quantum correlations including quantum entanglement [1][2][3][4][5][6][7], Bell nonlocality measured by the violation of the famous Clauser-Horne-Shimony-Holt (CHSH) inequality [8] and its relation to quantum entanglement [9][10][11][12][13][14][15][16], quantum discord [17,18] for the bipartite systems have been studied intensely, which is also generalized to the multipartite system for quantum entanglement [19][20][21][22][23][24][25][26] and the Bell nonlocality [27][28][29][30][31][32][33][34]. It has been shown that the Bell nonlocality may be stricter than quantum entanglement in the bipartite system [9][10][11][12][13][14][15][16] and tripartite system [32].…”
Section: Introductionmentioning
confidence: 99%